2010
DOI: 10.1179/crn.2010.019
|View full text |Cite
|
Sign up to set email alerts
|

Bifid Condyle: Review of the Literature of the Last 10 Years and Report of Two Cases

Abstract: Bifid mandibular condyle is a rare anomaly; there are several theories about its etiology, and it has been studied in both prehistoric and historic skulls, as well as in living human beings. It is a frequent, although unexpected, finding in asymptomatic individuals during radiological treatment. Presented here is a review of the literature over the past 10 years and two new cases of unilateral bifid condyle. Computerized tomography is usually considered the test of choice for establishing the differential diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…This case report of bilateral BMC is consistent with the most contemporaneous description of the entity as reported by Lopez-Lopez et al, 10 in which the secondary condylar heads arise from the respective necks of the mandible. However, with the recent upsurge in reporting of BMC, a wide variety of other presentations have been noted and so the exact definition of BMC remains controversial.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This case report of bilateral BMC is consistent with the most contemporaneous description of the entity as reported by Lopez-Lopez et al, 10 in which the secondary condylar heads arise from the respective necks of the mandible. However, with the recent upsurge in reporting of BMC, a wide variety of other presentations have been noted and so the exact definition of BMC remains controversial.…”
Section: Discussionsupporting
confidence: 79%
“…This appearance is consistent with the most contemporaneous description of the entity, as provided by Lopez-Lopez et al, 10 and we are the first research group to substantiate their thesis using three-dimensional (3D) CT colour-enhanced images which specifically delineate the exact anatomical landmarks that must be assessed in order to arrive at this diagnosis.…”
Section: Introductionsupporting
confidence: 54%
“…The exact etiology is unknown, but circumstances such as trauma, teratogenic drug use, genetic tendency, infection and exposure to radiation have been identified as possible causes for these variations (9,10). Others reported that BMC could be an embryological malformation (8,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature revealed 112 cases of BMC in living subjects (2,(4)(5)(6)(7)(8). BMC is usually diagnosed as an incidental finding during routine radiographic examination and typically has no distinct clinical symptoms (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] BMC is asymptomatic in many patients, often being detected on routine dental radiography, [3][4][5] however some individuals with BMC deformity suffer difficulties with occlusion and mastication that may require surgical intervention to allow restoration of temporomandibular function. [6,7] Bilateral BMC, although rare, has been reported, [7][8][9][10][11][12] and several cases of BMC associated with temporomandibular joint ankylosis have been published.…”
Section: Introductionmentioning
confidence: 99%